2021
DOI: 10.1200/jco.21.00143
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Considerations for Older Adults With Cancer: A Multidimensional, Multiphase Pathway to Improve Care

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 98 publications
0
32
0
Order By: Relevance
“…Various frailty instruments that can be used at the point of care for screening are available and have been shown to be accurate, feasible, and easily integrated in routine clinical practice and workflow. [77][78][79][80] Of note, the differences in long-term outcomes between patients with and without frailty should not lead to the conclusion that surgery is not indicated or is not worth the risk in the presence of frailty. Rather, acknowledgment of frailtyspecific risks should allow an individualized, patient-centered discussion with patients to determine whether surgery is indicated and desired.…”
Section: Discussionmentioning
confidence: 99%
“…Various frailty instruments that can be used at the point of care for screening are available and have been shown to be accurate, feasible, and easily integrated in routine clinical practice and workflow. [77][78][79][80] Of note, the differences in long-term outcomes between patients with and without frailty should not lead to the conclusion that surgery is not indicated or is not worth the risk in the presence of frailty. Rather, acknowledgment of frailtyspecific risks should allow an individualized, patient-centered discussion with patients to determine whether surgery is indicated and desired.…”
Section: Discussionmentioning
confidence: 99%
“…There remains a need to pursue the implementation of geriatric assessment in routine surgery practice and to improve the subsequent geriatric care. This approach should aim to define how pre‐operative geriatric assessment can guide the use of minimally invasive approaches and, when combined with tailored recovery protocols, how this assessment can reduce surgical stress and promote functional recovery [108].…”
Section: Improving the Treatment Of Established Cancers In Ageing Pat...mentioning
confidence: 99%
“…On the bright side, this study addresses an important question about the longterm probability of not living at home after surgery, which is an important matter for older adults who benefit from personalized care. 6 Also important to highlight is that this study was well constructed and involved a large population that included multiple cancer types from comprehensive databases available in Ontario, Canada. A previous study from this same group with a similar population showed that 5 years after surgical resection for cancer, 20% of patients died of cancer and 16% died of other causes.…”
Section: See Page 1223 For Related Articlementioning
confidence: 99%
“…Surgical intervention is safe and can have a positive impact on older adults with adequate risk stratification. 6 But this is definitely not the case for vulnerable or frail patients who are at high risk of experiencing complications and death in the postoperative period.…”
Section: See Page 1223 For Related Articlementioning
confidence: 99%